Exploring the landscape and climatic conditions of Neanderthals and anatomically modern humans in the Middle East: the rodent assemblage from the late Pleistocene of Kaldar Cave (Khorramabad Valley, Iran). (15th May 2020) - Rey-Rodríguez, Iván; López-García, Juan-Manuel; Blain, Hugues-Alexandre; Stoetzel, Emmanuelle; Denys, Christiane; Fernández-García, Mónica; Tumung, Laxmi; Ollé, Andreu; Bazgir, Behrouz
Abstract: The Middle East, specially the Zagros region, lies in a strategic position as a crossroads between Africa, Europe and eastern Asia. The landscape of this region that prevailed around the Neanderthal and anatomically modern human occupations is not well known. Only a few sites have been studied in detail in this area, often providing only a faunal list. These reveal that Neanderthals and anatomically modern humans lived in a landscape mainly composed of dry steppes. Here we extend the data obtained from Kaldar Cave through a systematic study of the rodent assemblage. The site provided evidence of a Pleistocene occupation attested by lithic tools associated with the Middle and Upper Palaeolithic, but it was also occupied during the Holocene, as evidenced by Neolithic artefacts. First excavations have revealed small vertebrates in Layer 4 (sub-layer 5 and 5II), belonging to the Upper Palaeolithic, and Layer 5 (sub-layers 7 and 7II), belonging to the Middle Palaeolithic. The rodent assemblage of Kaldar Cave is mainly composed of six arvicoline, two cricetine, one glirid, one dipodid, one gerbilline and two murine species. This assemblage shows that during the Late Pleistocene the environment around the site was mainly composed of open dry steppes, as indicated by the most abundant taxa, Microtus, Ellobius and Meriones . However, murine species indicate the presence of a vegetation cover. The palaeoclimatic conditions are characterized by lower temperatures and also less precipitation than at present. The results obtained with the rodent assemblages show that there is no major palaeoenvironmental or palaeoclimatic change that would explain the cultural shift between Layer 5 (Middle Palaeolithic) and Layer 4 (Upper Palaeolithic). Highlights: Middle East is a prime location to study Neanderthal and AMH activity. Kaldar is a key-site for the Middle/Upper Paleolithic transition in the Middle East. Ecological data inferred from rodents with Habitat Weighting and Bioclimatic Model . Neanderthals and AMH lived in dry steppes with patches of forested areas. No major environmental differences between the Middle and the Late Palaeolithic.